Posttraumatic stress disorder symptoms among healthcare workers during the Omicron era - Yin, YuanYuan; Han, Sizhu; Guan, Jiaoqiong; Wang, DuanWei; Wang, HaiRong; Yuan, Ti-Fei; Yang, Ying (Frontiers in Psychiatry, 2023)
Background The COVID-19 pandemic has caused significant psychological stress among healthcare workers. This study aimed to clarify the factors that influenced health workers’ posttraumatic stress disorder (PTSD) symptoms. Method A total of 443 healthcare workers from eight Mental Health Centers in Shandong were recruited to attend an online survey. Participants completed self-evaluation measures of exposure to the COVID-19 environment and PTSD symptoms, as well as measures of potential protective factors such as euthymia and perceived social support. Results About 45.37% of healthcare workers had severe symptoms of PTSD symptoms. Healthcare workers with more serious PTSD symptoms were significantly related to higher exposure to COVID-19 (r = 0.177, p < 0.001), as well as lower levels of euthymia (r = −0.287, p < 0.001) and perceived social support (r = −0.236, p < 0.001). The structural equation model (SEM) further revealed that the impact of exposure to COVID-19 on PTSD symptoms was partially mediated by euthymia, and moderated by perceived social support, especially from others (e.g., friends, leaders, relatives and colleagues). Conclusion These findings suggested that improving the state of euthymia, getting social support from others could alleviate PTSD symptoms among healthcare workers during the COVID-19.